Enhancement of stratospheric aerosols after solar proton event. - Henriksen, K.; Shumilov, O.I.; Kasatkina, E.A.; Vashenyuk, E.V. (European Geophysical Society, 1996)
The lidar measurements at Verhnetulomski observatory (68.6¡N, 31.8¡E) at Kola peninsula detected a considerable increase of stratospheric aerosol concentration after the solar proton event of GLE (ground level event) type on the 16/02/84. This increase was located at precisely the same altitude range where the energetic solar protons lost their energy in the atmosphere. The aerosol layer formed precipitated quickly (1Ð2 km per day) during 18, 19, and 20 February 1984, and the increase of R(H) (backscattering ratio) at 17 km altitude reached 40% on 20/02/84. We present the model calculation of CN (condensation nuclei) altitude distribution on the basis of an ion-nucleation mechanism, taking into account the experimental energy distribution of incident solar protons. The meteorological situation during the event was also investigated.